The Dilemma of Dual Citizenship Plan in Indonesia: An Overview of Politics and Human Rights - Ramdhani, Hilal; Novian, Rayhan Musa (Journal Public Policy, 2023)
The development of globalization has had an impact on the perspectives of Indonesian citizens, especially diaspora groups who wish to apply a dual citizenship legal status, because it is considered to have a positive impact on their lives. Pressure from diaspora groups has received various rejections from nationalist groups who view the implementation of dual citizenship as a potential threat to security and political instability in Indonesia. The method used in this study is a library method that uses various previous studies as a research data base. This study uses the political theory of citizenship initiated by Stokke, that citizenship has four dimensions, namely legal status, rights, membership, and participation related to the plan to implement dual citizenship in Indonesia, especially from a political and human rights perspective. The results of the study show that empirically dual citizenship prioritizes aspects of human rights, especially state protection for diaspora groups and returning the rights of citizens who were exiled due to politics in the New Order era. However, the application of dual citizenship also requires special studies, especially regarding political rights, because it involves various fundamental issues within the Indonesian state, such as getting the opportunity to vote and be elected in general elections. The basic problem is also related to the clarity of the ideology of dual citizenship, because only Indonesia implements Pancasila as the state ideology. The conclusion of the research results shows that political and human rights views have become a debate used by groups that oppose or support the plan to implement dual citizenship in Indonesia.